Evaluating the incidence of spinal cord injury after spinal cord stimulator implant: an updated retrospective review. Issue 7 (28th March 2022) - Hussain, Nasir; Gill, Jatinder; Speer, Jarod; Abdel-Rasoul, Mahmoud; Abd-Elsayed, Alaa; Khan, Safdar; Nguyen, Anthony; Simopoulos, Thomas; Weaver, Tristan
Abstract : Introduction: While spinal cord stimulator implant is an increasingly safe procedure, one of the most feared complications is spinal cord injury. Still, literature regarding its incidence remains highly variable. This retrospective analysis aims to evaluate the incidence of spinal cord injury after spinal cord stimulator implant using a large-scale claims database. Methods: The PearlDiver-Mariner database of national all payer claims was used to identify patients who underwent spinal cord stimulator implant (percutaneous or paddle) and developed subsequent spinal cord injury within 45 days. The primary outcome was to determine the overall incidence of spinal cord injury after spinal cord stimulator implant. Secondary outcomes included an evaluation of potential factors associated with developing spinal cord injury using univariable and multivariable regression analysis. Results: A total of 71, 172 patients who underwent a spinal cord stimulator implant were included in the analysis, of which 52, 070 underwent percutaneous and 19, 102 underwent paddle spinal cord stimulator lead implant. The overall incidence of spinal cord injury after spinal cord stimulator implant (any lead type) was found to be 0.42% (302 patients). The incidence of spinal cord injury after percutaneous and paddle lead implants did not differ at 0.45% (233 patients) and 0.36% (69 patients)(p=0.12), respectively. Overall, variables associated with a significantly increased OR (95% confidence interval) of developing spinal cord injury included male gender by 1.31 times (1.04 to 1.65)(p=0.02); having a claim for low molecular weight heparin within 30 days by 3.99 times (1.47 to 10.82)(p<0.01); a diagnosis for osteoporosis within 1 year by 1.75 times (1.15 to 2.66)(p<0.01); and a diagnosis of cervical or thoracic spinal canal stenosis within 1 year by 1.99 (1.37 to 2.90)(p<0.001) and 4.00 (2.63 to 6.09)(p<0.0001) times, respectively. Conclusions: Overall, our results support the notion that spinal cord stimulator implant continues to be a safe procedure for chronic pain patients. However, risk factor mitigation strategies for the prevention of spinal cord injury after spinal cord stimulator implant should be undertaken prior to performing the procedure.